2018
DOI: 10.1016/j.ejc.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Stability results for graphs with a critical edge

Abstract: The classical stability theorem of Erdős and Simonovits states that, for any fixed graph with chromatic number k + 1 ≥ 3, the following holds: every n-vertex graph that is H-free and has within o(n 2 ) of the maximal possible number of edges can be made into the k-partite Turán graph by adding and deleting o(n 2 ) edges. In this paper, we prove sharper quantitative results for graphs H with a critical edge, both for the Erdős-Simonovits Theorem (distance to the Turán graph) and for the closely related question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 13 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…As far as we know, the above results in [15,41] and some recent work of Norin and Yepremyan [33,34] (who considered the Turán problem for hypergraphs) are the only known examples where perfect stability was established for a non-trivial problem. Furthermore, almost all proofs where the classical stability and the exact result were derived from a flag algebra computation were rather ad-hoc and taylored to a particular problem.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…As far as we know, the above results in [15,41] and some recent work of Norin and Yepremyan [33,34] (who considered the Turán problem for hypergraphs) are the only known examples where perfect stability was established for a non-trivial problem. Furthermore, almost all proofs where the classical stability and the exact result were derived from a flag algebra computation were rather ad-hoc and taylored to a particular problem.…”
Section: Introductionmentioning
confidence: 67%
“…By (43) and recalling that we are only interested in points that belong to the interior of D, we get that x 3 = 1 − x 1 − x 2 − x 3 , while by subtracting (41) and (42), we get that x 1 = x 2 . Combining these two we get, in particular, that x 1 +x 3 = 1/2.…”
Section: Lemma 84mentioning
confidence: 99%
See 1 more Smart Citation
“…In [11] Füredi's result was strengthened for some values of r. Roberts and Scott [15] showed that D r (G) = O(t 3/2 /n) when t δn 2 , and that this result is sharp up to a constant factor. They also proved a more general result for H-free graphs where H is an edge-critical graph.…”
Section: Theorem 11 (Erdős Győri and Simonovits [7]mentioning
confidence: 99%
“…K r and r-chromatic graphs with a color-critical edge often behave similarly in extremal questions, see e.g. [17] and see [16] for several stability results. Another reason to assume that this conjecture might hold, and it might be easier to prove this than Conjecture 1.3 is the following.…”
Section: Introductionmentioning
confidence: 99%